2008
DOI: 10.1111/j.1551-2916.2008.02779.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties of a New Ultra Low Loss Pervoskite Ceramic

Abstract: The microwave dielectric properties and microstructures of an Mg(Zr 0.05 Ti 0.95 )O 3 ceramic system have been investigated. The compounds were prepared by the conventional solid-state route, and sintered at 13601-14501C for 2-6 h. The structure and microstructure were analyzed using X-ray diffraction and scanning electron microscopy techniques. The Mg(Zr 0.05 Ti 0.95 )O 3 had excellent dielectric properties: Q Â f 5 380 000 (GHz), e r 5 18.1, and s f 5 À50 ppm/1C for the sample at 14201C/4 h. These properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 13 publications
0
28
1
Order By: Relevance
“…The abnormal grain growth was obtained especially at higher B 2 O 3 content for higher sintering temperature. These may directly affect the [3]. It can be also observed that Mg 2 TiO 4 (spot C) and MgTi 2 O 5 (spot D) phase exists in 0.5 and 1.0 wt% (appeared at 1390 • C) B 2 O 3 -doped MZrT sample, respectively.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The abnormal grain growth was obtained especially at higher B 2 O 3 content for higher sintering temperature. These may directly affect the [3]. It can be also observed that Mg 2 TiO 4 (spot C) and MgTi 2 O 5 (spot D) phase exists in 0.5 and 1.0 wt% (appeared at 1390 • C) B 2 O 3 -doped MZrT sample, respectively.…”
Section: Resultsmentioning
confidence: 74%
“…This indicates that B 2 O 3 addition effectively improves the sinterability of MZrT ceramics. The 4.53 g/cm 3 of the bulk density is obtained for pure MZrT sintering at 1420 • C for 4 h [3]. The maximum bulk density obtained decreases with the increase of B 2 O 3 content.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…To further investigate the influence of equivalent-charge substitutions for B sites on MgTiO 3 , we used Zr 4+ to substitute Ti 4+ to form Mg(Zr 0.05 Ti 0.95 )O 3 (MZrT) in the previous study. Excellent microwave dielectric properties of ε r = 18.1, Q × f = 380,000 GHz and f = −50 ppm/ • C were obtained for the Mg(Zr 0.05 Ti 0.95 )O 3 ceramics [2]. However, it required sintering temperatures as high as 1420 • C. For practical application in communication systems, it is necessary to lower the sintering temperature of Mg(Zr 0.05 Ti 0.95 )O 3 ceramics.…”
Section: Introductionmentioning
confidence: 97%